Eriophyoid mites (Acari: Prostigmata: Eriophyoidea) from Hungary: a new species on Agrimonia eupatoria (Rosaceae) and new record on Convolvulus arvensis (Convolvulaceae) - Ripka, Géza (Zootaxa, 2014)
A new species of eriophyoid mite, Aculus castriferrei n. sp., associated with Agrimonia eupatoria (Rosaceae) is described and illustrated from Hungary. Morphological differences distinguishing this vagrant species from other rosaceous inhabiting congeners are discussed. Aceria malherbae Nuzzaci is a new record for the eriophyoid fauna of Hungary after it was found causing severe damage symptoms to Convolvulus arvensis L. (Convolvulaceae).